Extensive secondary contact among three glacial lineages of Arctic Char (Salvelinus alpinus) in Labrador and Newfoundland. Issue 4 (28th January 2019) - Salisbury, Sarah J.; McCracken, Gregory R.; Keefe, Donald; Perry, Robert; Ruzzante, Daniel E.
Abstract: Aim: The Pleistocene glaciation event prompted the allopatric divergence of multiple glacial lineages of Arctic char ( Salvelinus alpinus ), some of which have come into secondary contact upon their recolonization of the Holarctic. While three glacial lineages (Arctic, Atlantic, and Acadian) are known to have recolonized the western Atlantic, the degree of overlap of these three lineages is largely unknown. We sought to determine the distribution of these three glacial lineages in Labrador and Newfoundland at a fine spatial scale to assess their potential for introgression and their relative contribution to local fisheries. Location: Labrador and Newfoundland, Canada. Methods: We sequenced a portion of the D‐loop region in over 1, 000 Arctic char ( S. alpinus ) samples from 67 locations across Labrador and Newfoundland. Results: Within Labrador, the Arctic and Atlantic lineages were widespread. Two locations (one landlocked and one with access to the sea) also contained individuals of the Acadian lineage, constituting the first record of this lineage in Labrador. Atlantic and Acadian lineage individuals were found in both eastern and western Newfoundland. Multiple sampling locations in Labrador and Newfoundland contained fish of two or more different glacial lineages, implying their introgression. Glacial lineage did not appear to dictate contemporary genetic divergence between the pale and dark morph of char present in Gander Lake, Newfoundland. Both were predominately of the Atlantic lineage, suggesting the potential for their divergence in sympatry. Main conclusions: Our study reveals Labrador and Newfoundland to be a unique junction of three glacial lineages which have likely hybridized extensively in this region. Abstract : Using the D‐loop mitochondrial region, we investigated the extent and potential introgression of three glacial lineages (Arctic, Atlantic, and Acadian) of Arctic char in Labrador and Newfoundland at a fine spatial scale. Our results demonstrate the widespread secondary contact and introgression of these lineages despite thousands of years of allopatric divergence. Glacial lineage was not consistently different between two morphs found in Gander Lake, indicating the potential for the sympatric divergence of this morph pair from an ancestral population founded by multiple glacial lineages.